Using laser ultrasound to detect sub-surface defects in metal laser powder bed fusion components - Everton, Sarah K.; Dickens, Phill; Tuck, Christopher; Dutton, Ben (Springer, 2017)
Laser powder bed fusion offers many advantages over conventional manufacturing methods, such as the integration of multiple parts which can result in significant weight-savings. The increased design freedom that layer-wise manufacture allows has also been seen to enhance component performance at little or no added cost. However, for such benefits to be realised, the material quality must first be assured. Laser ultrasonic testing is a non-contact inspection technique which has been proposed as suitable for in-situ monitoring of metal additive manufacturing processes. This paper explores the current capability of this technique to detect manufactured, sub-surface defects in Ti-6Al-4V samples, ex-situ. The results are compared with x-ray computed tomography reconstructions and focus variation microscopy. Whilst laser ultrasound has been used to identify material discontinuities, further work is required before this technique could be implemented in-situ.